HIV-associated nephropathy: a diagnosis in evolution - Ray, Patricio E. (Oxford University Press, 2012)
HIV-1 associated nephropathy (HIVAN) is a clinical and renal histological disease characterized by the presence of heavy proteinuria associated with focal segmental glomerulosclerosis and microcystic tubular dilatation. These renal lesions lead to renal enlargement and rapid progression to kidney failure. People from African ancestry show a unique susceptibility to develop HIVAN. The study by Wearne and colleagues, which includes the largest group of patients of African ancestry with HIVAN studied so far, describes a novel renal histological variant of HIVAN, and suggests that antiretroviral therapies improve the clinical outcome of all HIV-associated renal diseases. These findings, when interpreted in the context of recent advances in our understanding of the molecular pathogenesis and genetics of HIVAN, will facilitate the recognition of all clinical variants of HIVAN as well the planning of better screening, prevention, and treatment programs for all HIV nephropathies.